Blood nesfatin-1 levels in patients with polycystic ovary syndrome: a systematic review and meta-analysis - Wang, Mei; Tong, Jiao; Zhu, Qing; Tang, Huaiyun; Tang, Lisha (Frontiers in Endocrinology, 2024)
Background: Previous studies have investigated the relationship between nesfatin-1 level and polycystic ovary syndrome (PCOS). However, these studies have produced conflicting results. Thus, in this meta-analysis, we aimed to clarify the association between blood nesfatin-1 levels and PCOS, and the ability of nesfatin-1 as a biomarker in PCOS. Methods: Meta-analysis was performed using STATA 12.0 software. We computed standard mean difference (SMD) and 95% confidence interval (CI) regarding the comparison of blood nesfatin-1 in patients with PCOS and controls. Results: The present meta-analysis showed no significant difference in blood nesfatin-1 level between patients with PCOS and controls with a random effects model (SMD = 0.03; 95%CI: -0.71, 0.77; I2 = 97.1%, p value for Q test < 0.001). Subgroup analysis for different ethnicities reported no significant difference in blood nesfatin-1 level between patients with PCOS and controls in both Caucasian and Asian populations. Subgroup analysis for different sample types reported no significant difference in serum nesfatin-1 level between patients with PCOS and controls. Subgroup studies reported no significant difference in blood nesfatin-1 level between PCOS and controls in both obese and non-obese populations. Conclusion: In conclusion, there is no significant relationship between blood nesfatin-1 levels and PCOS.